Raman spectroscopy of microbial pigments - Jehlička, Jan; Edwards, Howell G M; Oren, Aharon (Applied and environmental microbiology, 2014)
Raman spectroscopy is a rapid nondestructive technique providing spectroscopic and structural information on both organic and inorganic molecular compounds. Extensive applications for the method in the characterization of pigments have been found. Due to the high sensitivity of Raman spectroscopy for the detection of chlorophylls, carotenoids, scytonemin, and a range of other pigments found in the microbial world, it is an excellent technique to monitor the presence of such pigments, both in pure cultures and in environmental samples. Miniaturized portable handheld instruments are available; these instruments can be used to detect pigments in microbiological samples of different types and origins under field conditions.
Keywords: Ramanova spektroskopie; houby; Pigments, Biological; Bacteria; Archaea; Fungi; Spectrum Analysis, Raman; biologické pigmenty